50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three-Dimensional Plasma Actuation on the Wake of a Circular Cylinder

Abstract: Dielectric-barrier discharge plasma actuators were mounted on a circular cylinder in a square wave pattern for active forcing of the cylinder wake. The intermittent spacing of the buried electrodes created a spanwise modulated blowing profile, such that three-dimensional instabilities in the wake were targeted for control. Two distinct power levels of 5.6 and 13.6 watts were used for forcing the flow. Considerable spanwise variation in the wake was achieved with the lower power forcing when the actuators were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 31 publications
(27 reference statements)
0
17
1
Order By: Relevance
“…This particular finding has not been observed for other cases of experiments, namely low-and high-power continuous forcing and high-power, modulated forcing. It should be mentioned here that in earlier experiments with low-power continuous forcing 15 , the random attenuation of shedding peaks was not observed as was found in Figure 24.…”
Section: Velocity Profilescontrasting
confidence: 51%
See 4 more Smart Citations
“…This particular finding has not been observed for other cases of experiments, namely low-and high-power continuous forcing and high-power, modulated forcing. It should be mentioned here that in earlier experiments with low-power continuous forcing 15 , the random attenuation of shedding peaks was not observed as was found in Figure 24.…”
Section: Velocity Profilescontrasting
confidence: 51%
“…A particular characteristic of the flow in the low-power modulated forcing case will now be discussed. For all other test conditions (also for earlier continuous forcing experiments 15 ) it has been observed that close to the cylinder (less than x/d of 10) the time-averaged velocity profiles obtained by x-wire traverse were very regular in the sense all the data points could be nicely fitted by a single curve (let it be called a common fitting curve). This was because of the ordered nature of periodic shedding close to the cylinder.…”
Section: F Detailed Study Of Low Power Modulated Forcing (F M =2f 0 )mentioning
confidence: 94%
See 3 more Smart Citations